Separasi Aliran pada Permukaan Atas Airfoil Kumbang Kelapa dengan Metoda China Clay - Benny Dwika Leonanda (Department of Mechanical Engineering, Universitas Andalas, 2020)
This study is aimed at identifying airfoils by mimicking the curved shape of the wings of a flying animal. This interferes with what people did in ancient times to obtain objects capable of flying. The animal profile selected was the Coconut Beetle (Rhinkoporus Rhigidoporus). The wings were divided into nine pieces and made a wing model with a chord size of 15 cm, a length of 45 cm and tested in a subsonic force draft wind tunnel with a test section measuring 45 x 45 x 100 cm3. Tests are carried out to measure the length of flow separation on the upper surface of the airfoil at Reynolds and the different angles of attack of the airfoil. The China Clay method was used to determine the separation point on the airfoil surface, and the test results obtained various separation points for different angles of attack and Reynolds number.